Simultaneous spectrophotometric determination of dipyrone and caffeine in pharmaceutical formulations - (:unkn) unknown (My University, 1995)
A simple and rapid spectrophotometric method has been developed for simultaneous determination of dipyrone and caffeine without prior separation.